2005
DOI: 10.1097/00005082-200501000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Sliding Scale Diuretic Titration Protocol in Patients With Heart Failure

Abstract: Patients with heart failure (HF) are often instructed to temporarily adjust their diuretic dose. This approach has become routine in some HF management programs; however, no study has specifically examined the effects of a patient-directed flexible diuretic protocol. For the purposes of this study, patients were randomized into a usual care (UC) group (n = 31) or a flexible diuretic titration (DT) group (n = 35). The DT group completed a 6-item diuretic titration protocol once a day, for 3 months. The 6-minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Two of the articles focused only on improving self-care. 284,288 In the other 20 articles, self-care was emphasized as a part of a disease-management program. Only 18 of the 22 studies used a randomized design.…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Two of the articles focused only on improving self-care. 284,288 In the other 20 articles, self-care was emphasized as a part of a disease-management program. Only 18 of the 22 studies used a randomized design.…”
Section: Quality Of Lifementioning
confidence: 99%
“…When these 18 studies were reviewed, the effect of self-care interventions on QOL in HF patients was equivocal, with only 10 trials finding greater improvement in QOL in the intervention group than in the control group. In the 2 trials that tested self-care as the primary intervention, 1 reported improved QOL in the intervention group, 288 whereas the other reported no differences in QOL between groups. 284 Interestingly, QOL differences were found in studies that included relatively younger patients, predominantly men, and primarily New York Heart Association class III and IV patients.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Weaker self-efficacy beliefs are associated with nonadherence to self-care recommendations for HF. 47 The positive effect of such an intervention was seen in two studies: one study tested a sliding scale diuretic titration protocol in HF patients where patients using this self-management strategy had increases in their exercise tolerance, quality of life, and fewer emergency department visits; 48 and the other study admitted HF patients randomized to an HF management group and taught self-management skills compared with usual care. 49 Unfortunately, the majority of patients with HF are not followed in an HF disease management program but by primary care physicians.…”
Section: Clinical Perspectives: Benefits and Disadvantagesmentioning
confidence: 99%
“…Earlier smaller studies also have not shown any convincing evidence for self-management. [33][34][35][36] Therefore, a strategy that minimizes patient responsibility in monitoring and care might be more pragmatic. All strategies should still aim at having a patient-centered care plan along with stressing patient education.…”
Section: Home Monitoring -Is It An Epidemiologically Feasible Solution?mentioning
confidence: 99%